TEPID WATER SPONGE AND ALOE VERA COMPRESSES FOR REDUCING BODY TEMPERATURE IN TODDLERS: A COMPARATIVE STUDY - Oktaviona; Hamzah; Muthmainnah (Nursing Sciences Journal, 2025)
Infants often experience fever, which if left untreated can cause seizures. Febrile seizures can cause brain abnormalities. Non-pharmacological methods such as compresses are used to reduce fever, including tepid water sponges and aloe vera compresses, but further research is needed on which compress method is more effective in reducing fever. The purpose of this study was to analyze the effectiveness of tepid water sponges and aloe vera compresses in reducing body temperature in toddlers with febrile seizures. This study adopted a true experiment using a pretest-posttest design with two control groups, using purposive sampling. A sample of 30 people was taken from the population of toddlers treated at Dr. Doris Sylvanus Regional General Hospital. The instruments used were observation sheets, thermometers, aloe vera gel, SOP for tepid water sponges, and SOP for aloe vera compresses, which were analyzed using the Wilcoxon Rank and Mann Whitney tests. The results showed that there was a significant decrease in body temperature with the tepid water sponge intervention and the aloe vera compress intervention. Based on the mean rank for aloe vera compresses > than the mean rank for tepid water sponges, it means that aloe vera compresses are more effective than tepid water sponges, so they can be recommended as a safe and easy-to-apply non-pharmacological method. Healthcare workers and families are advised to use aloe vera compresses as a practical alternative for treating fever in toddlers at home and in healthcare facilities, and to integrate them into education and guidelines for caring for children with fever.